Brief Disruption of Circadian Rhythms Alters Intestinal Barrier Integrity and Modulates DSS-Induced Colitis Severity in Mice - Barrios, Bibiana E.; Jaime, Cristian E.; Sena, Angela A.; de Paula-Silva, Marina [UNESP]; Gil, Cristiane D.; Oliani, Sonia M. [UNESP]; Correa, Silvia G. (Springer Nature, 2024)
Physiological processes in organisms exhibit circadian rhythms that optimize fitness and anticipate environmental changes. Luminal signals such as food or metabolites synchronize bowel activity, and disruptions in these rhythms are linked to metabolic disorders and gastrointestinal inflammation. To characterize the intrinsic intestinal rhythms and assess disruptions due to continuous darkness or light exposure, C57BL/6 mice were exposed to standard light–dark conditions or continuous light/darkness for 48 h, with evaluations at four timepoints. We assessed intestinal morphology, mucus production, nitric oxide levels and permeability. Under standard light: dark cycles, mice showed changes in intestinal morphology consistent with normal tract physiology. Continuous light exposure caused marked alterations in the small intestine´s epithelium and lamina propria, reduced nitric oxide production in the colon, and predominant neutral mucins. Enhanced permeability was indicated by higher FITC-dextran uptake and increased frequency of IgG-coated bacteria. Additionally, the 48 h-disruption influenced DSS-induced colitis with attenuation in L:L group, or exacerbation in D:D group, of clinical signs. These findings highlight the critical role of circadian rhythms in gut histoarchitecture and function, demonstrating that short-term disruptions in light–dark cycles can compromise intestinal barrier integrity and impact inflammatory outcomes.
Keywords: Inflammation; Intestine; Mice; Mucus; Permeability; Rhythm